2020
DOI: 10.21203/rs.3.rs-42067/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MicroRNA-219c-5p Regulates Bladder Fibrosis by Targeting FN1

Abstract: BackgroundWe found that the bladders of multiple sclerosis mice were significantly fibrotic. This study aimed to investigate the relationship between fibronectin 1 (FN1) and bladder fibrosis, as well as the microRNAs involved in FN1 regulation. Methods The degree of bladder smooth muscle fibrosis was observed by immunohistochemistry. In addition, we used quantitative real-time polymerase chain reaction (RT-qPCR) and Western blotting to determine FN1 expression in bladders with different grades of fibrosis. Bio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…However, its underlying mechanisms remain unclear. FN1 and SERPINE1, known to be fibrosis-related factors, play an important role in the development of fibrotic diseases [27][28][29]. Studies have shown that the expression of FN1 and SERPINE1 can be induced by epigenetic activation mechanisms downstream of TGFb, which promotes fibrosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, its underlying mechanisms remain unclear. FN1 and SERPINE1, known to be fibrosis-related factors, play an important role in the development of fibrotic diseases [27][28][29]. Studies have shown that the expression of FN1 and SERPINE1 can be induced by epigenetic activation mechanisms downstream of TGFb, which promotes fibrosis [30].…”
Section: Discussionmentioning
confidence: 99%